Translation of green supply chain management to environmental performance via green process innovation and the moderation of Managers' job satisfaction and top management commitment - Mohammad Salameh M. Alhmeidiyeen; Faisal Qadeer; Imran Hameed; Muhammad Akram Naseem (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
This paper investigates the effects of green strategy and design (i.e., two important facets of green supply chain management) on firms' environmental performance through the mediating role of green process innovation. In addition, the moderation of two management attitudes (managers' job satisfaction and top management commitment) are tested as the boundary conditions of the proposed relationships. A time-lag design was used to collect data from 279 managers of 31 manufacturing firms in Jordan. SPSS and PROCESS macro were utilized to test hypothesized relationships. All hypothesized mediation and moderation relations were supported, except the moderation of top management commitment to the green design-green process innovation relationship. These findings provide managers with evidence to proactively implement and invest in green strategy and green design facets because such facets will not only positively affect their environmental performance but enhance other performances and help achieve a competitive advantage for the firm. Our findings expand the literature on green strategy and design facets. It is among the few studies that have explored the link between green strategy and environmental performance, the underlying process, and introducing two managerial attitudes (middle manager job satisfaction and top management commitment) as boundary conditions in a single study. The testimony from the Jordanian manufacturing sector is another unique contribution to this study.
Keywords: 330; Green strategy; green design; green process innovation; supervisors' jobsatisfaction; top management commitment; environmental performance